Consequences on the right ventricular to pulmonary circulation coupling of COVID-19 infection. (14th October 2021) - Vella, A M; Bursi, F; Santangelo, G; Barbieri, A; Toriello, F; Valli, F; Sansalone, D; Carugo, S; Guazzi, M
Abstract: Background: Right Ventricular (RV) dysfunction and pulmonary hypertension (PH) are two very likely acute and long term targets of COVID-19 pneumonia, with a potential prognostic implications. Purpose: To determine the COVID-19 pneumonia effects on the right ventricular to pulmonary circulation coupling through bedside echocardiography and extend its implications to prognostic assessment. Methods: Single-centre study including consecutive subjects hospitalized for COVID-19 pneumonia who underwent a clinical indicated echocardiogram between March 2020 and December 2020. Extensive analysis of cardiac function was performed offline by an operator blinded to clinical data, laboratory findings and CT scans. Results: 133 patients were enrolled (mean age 69±12 years, 57% men), 38% of whom already had cardiac disease in their medical history. In-hospital mortality was 26% (35 pts), during a mean hospital stay of 26±16 days. Non survivors had higher pulmonary artery systolic pressure (PASP) and worse RV function, assessed with both standard parameters (i.e. TAPSE) and with the novel speckle tracking analysis by RV-Global Longitudinal Strain (RV-GLS) and RV-Free Wall Longitudinal Strain (RV-FWLS). The combination of these two variables in TAPSE/PASP ratio allows assessment of RV to pulmonary circulation (Pc) coupling and was strongly associated with in-hospital death (HR 0.73, 95% CI 0.59–0.89, p=0.003) and patients with TAPSE/PASP<0.57 mm/mmHg had a more than 4-fold increased risk of in-hospital death (HR 4.8, 95% CI 1.7–13.1, p=0.003). In patients where speckle tracking analysis was feasible, we examined RV-GLS/PASP and RV-FWLS/PASP and found that it was associated with in-hospital mortality. The best cut-offs for predicting in-hospital mortality was 0.51 for RV-GLS/PASP (94% sensitivity and 59% specificity) and 0.49 for RV-free wall LS (87% sensitivity and 70% specificity). At the multivariable analysis RV to Pc remained associated with in-hospital death after adjustments for age, PaO2/FiO2, LVEF, and severity of lung involvement at the CT. Conclusions: Either PH and RV dysfunction predict in-hospital mortality in patients with COVID-19 pneumonia. The assessment of RV to Pc coupling, however, better describes the adaptive RV response to increased PASP and gives additional prognostic information in a population with a relevant prevalence of comorbidities. FUNDunding Acknowledgement: Type of funding sources: None.